The Mechanical Glass Transition Temperature Affords a Fundamental Quality Control in Condensed Gels for Innovative Application in Functional Foods and Nutraceuticals - Vilia Darma Paramita; Naksit Panyoyai; Stefan Kasapis (Foods, 2025)
A subject of increasing fundamental and technological interest is the techno- and bio-functionality of functional foods and nutraceuticals in high-solid gels. This encompasses the diffusion of natural bioactive compounds, prevention of oxidation of essential fatty acids, minimization of food browning, and the prevention of malodorous flavour formation in enzymatic and non-enzymatic reactions, to mention but a few. Textural and sensory considerations require that these delivery/encapsulating/entrapping vehicles are made with natural hydrocolloids and co-solutes in a largely amorphous state. It is now understood that the mechanical glass transition temperature is a critical consideration in monitoring the performance of condensed polymer networks that incorporate small bioactive compounds. This review indicates that the metastable properties of the rubber-to-glass transition in condensed gels (as opposed to the thermodynamic equilibrium in crystalline lattices) are a critical parameter in providing a fundamental quality control of end products. It appears that the “sophisticated synthetic polymer research” can provide a guide in the design of advanced biomaterials for targeted release or the prevention of undesirable byproducts. Such knowledge can assist in designing and optimizing functional foods and nutraceuticals, particularly those including vitamins, antioxidants, essential fatty acids, stimulants for performance enhancement, and antimicrobials.